Mediterranean agro-pastoral systems and agro-ecology: A cross-analysis of two situations in Corsica and in the argane tree area in Morocco - Dubeuf J.-P. (Pastoralism and sustainable development: proceedings, 2021)
Agro-ecology is the way of designing agricultural production systems by relying on the functionalities offered by ecosystems. Today, it stands out as the direction to take to meet the challenges of preserving natural resources and combating or adapting to climate changes. Our objective is to explore to what extent agro-pastoral systems in the Mediterranean could be involved into this agro-ecological approach. After presenting the general principles of agro - ecology in its different environmental as well as social, economic and societal dimensions, we analyze and compare two examples of Mediterranean agro-pastoralism. The first case is Corsica, a French island located in the North-Western part of the Mediterranean, the second one is in the South- West of Morocco in the argane tree biosphere reserve. From this comparative analysis, a holistic diagnosis of the strengths of pastoral systems but also of their challenges is proposed. Some prospective scenarios are then discussed on the possible futures of these systems and the dynamics to impulse.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)